2013
DOI: 10.1021/ac400639y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in Analytical Chemistry: Host–Guest Type Molecular Recognition

Abstract: Cyclodextrins are utilized in many diverse fields of analytical chemistry, due to their propensity to form reversible inclusion complexes and recognize analytes selectively. This Feature shows how these nanocavities can serve analysts in sample preparation, sensitivity and selectivity improvement, enantio-separation, creating single-molecule sensors, and automatizing DNA sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(135 citation statements)
references
References 56 publications
0
132
0
Order By: Relevance
“…Nanocomposites of β-cyclodextrin (β-CD) and multi-walled CNT (MWCNT) have recently been successfully used to study and quantify a variety of organic molecules owing to the synergistic effect of both materials [14][15][16][17]. The usefulness of CDs is related to their unique structures and to the fact that CDs retain their analyterecognizing and entrapping properties under a relatively broad range of experimental conditions [18][19][20][21][22]. The interfacial architecture and electrochemical activity of CNT-modified electrodes after incorporating CDs and the resulting recognition effects have already been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites of β-cyclodextrin (β-CD) and multi-walled CNT (MWCNT) have recently been successfully used to study and quantify a variety of organic molecules owing to the synergistic effect of both materials [14][15][16][17]. The usefulness of CDs is related to their unique structures and to the fact that CDs retain their analyterecognizing and entrapping properties under a relatively broad range of experimental conditions [18][19][20][21][22]. The interfacial architecture and electrochemical activity of CNT-modified electrodes after incorporating CDs and the resulting recognition effects have already been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that the sensitivity of PANIeCNT composite sensors can be improved by incorporation of CDs (Rahemi et al, 2012(Rahemi et al, , 2013. The usefulness of CDs is related to their unique structures and to the fact that CDs retain their analyte-recognizing and entrapping properties under a relatively broad range of experimental conditions (Szente & Szem an, 2013). The interfacial architecture and electrochemical activity of PANI/CNT-modified electrodes after incorporating CDs and the resulting recognition effects were already reported (Rahemi et al, 2012(Rahemi et al, , 2013Shen & Wang, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…showing high molecular selectivity and enantioselectivity (Harada et al, 2014;Szente and Szemán, 2013;Xie et al, 2015;Yang et al, 2015). Therefore, if a CNTs-GNRs/CDs composite, possessing the synergistic effects from CNTs-GNRs and CDs, could be produced and used in electrochemical sensing of 2-and 4-AP, it would be possible to achieve the highly sensitive and simultaneous electrochemical determination of 2-and 4-AP.…”
Section: Introductionmentioning
confidence: 99%